2023
DOI: 10.1186/s12864-023-09330-4
|View full text |Cite
|
Sign up to set email alerts
|

Employing computational tools to design a multi-epitope vaccine targeting human immunodeficiency virus-1 (HIV-1)

Hamza Sher,
Hafsa Sharif,
Tahreem Zaheer
et al.

Abstract: Background Despite being in the 21st century, the world has still not been able to vanquish the global AIDS epidemic, and the only foreseeable solution seems to be a safe and effective vaccine. Unfortunately, vaccine trials so far have returned unfruitful results, possibly due to their inability to induce effective cellular, humoral and innate immune responses. The current study aims to tackle these limitations and propose the desired vaccine utilizing immunoinformatic approaches that have retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…Furthermore, pre-clinical studies using animal models and a multiple-epitope Epstein-Barr virus vaccination showed encouraging outcomes [33]. Similar to our current work, a multiple-epitope vaccine that is specially designed to target HIV-1 has also been created [34].…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, pre-clinical studies using animal models and a multiple-epitope Epstein-Barr virus vaccination showed encouraging outcomes [33]. Similar to our current work, a multiple-epitope vaccine that is specially designed to target HIV-1 has also been created [34].…”
Section: Discussionsupporting
confidence: 65%